2018
DOI: 10.1182/blood-2018-99-115609
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Foundation and Federal Support and Development of New Therapeutics for Sickle Cell Disease and Cystic Fibrosis

Abstract: BACKGROUND: Sickle cell disease (SCD) and cystic fibrosis (CF) are rare inherited disorders of similar severity. Disparities in funding between these two diseases have been long recognized and likely contribute to limited access to care and treatments for sickle cell disease. Private investment in therapeutics for these and other orphan diseases has greatly increased in the past ten years. We hypothesized that these increased private expenditures may help correct disparities in research publications, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For example, sickle cell disease and cystic fibrosis are both genetic disorders of similar severity, but sickle cell disease is more common in Black patients, while cystic fibrosis is more common in white patients. In the United States, however, cystic fibrosis receives 3.4 times more funding per affected individual from the US National Institutes of Health (NIH), the largest funder of US clinical research, and hundreds of times more private funding (37). The disparities in funding persist despite the 1972 Sickle Cell Anemia Control Act, which recognizes that sickle cell has been neglected by the wider research community.…”
Section: Racial Injusticementioning
confidence: 99%
“…For example, sickle cell disease and cystic fibrosis are both genetic disorders of similar severity, but sickle cell disease is more common in Black patients, while cystic fibrosis is more common in white patients. In the United States, however, cystic fibrosis receives 3.4 times more funding per affected individual from the US National Institutes of Health (NIH), the largest funder of US clinical research, and hundreds of times more private funding (37). The disparities in funding persist despite the 1972 Sickle Cell Anemia Control Act, which recognizes that sickle cell has been neglected by the wider research community.…”
Section: Racial Injusticementioning
confidence: 99%
“…In this respect, another important aspect, in terms of minority groups' access to adequate healthcare, may be the lack of interest in developing new therapeutic options for diseases more prevalent in minority groups, due to structural racism embedded in the world of research and in drug development. From our perspective, Farooq and Strouse [68] gave an excellent example of potential racial bias in research and drug development by comparing two distinct diseases, each one predominantly affecting a different racial group.…”
Section: Third Node: Influence Of Structural Racism On Deliverables Omentioning
confidence: 99%
“…stroke) [70]. Although both conditions have similar disease severity, and a lower percentage of patients in the United States suffers from cystic fibrosis in comparison to SCD, Farooq and Strouse [68] demonstrated that there are wide disparities in how funding was allocated for research by the National Institutes of Health (NIH) and private Foundations to study the two diseases. Moreover, research productivity in terms of PubMed-indexed articles and drug approvals were significantly higher for cystic fibrosis than for SCD, in spite that both diseases have similar numbers of clinical trials [68].…”
Section: Third Node: Influence Of Structural Racism On Deliverables Omentioning
confidence: 99%
“…For example, Sickle Cell disease impacts mainly the Black population while cystic fibrosis impacts mainly the white population. Cystic fibrosis receives significantly more funding and research resources, despite both being genetic disorders of similar severity [14,19,48].…”
Section: Motivationmentioning
confidence: 99%